Benefits of robotic gait assistance with ATLAS 2030 in children with cerebral palsy - Castro, Pilar; Martí, María; Oliván-Blázquez, Bárbara; Boñar, Nuria; García, Violeta; Gascón-Santos, Santiago; Panzano, Alicia; Vela, Sara; Tajadura, Sara; Peña, Ana; Tris-Ara, María Josefa (Frontiers in Pediatrics, 2024)
Objective: This study aims to assess the impact of integrating ATLAS 2030 into the conventional therapy regimen for children with Cerebral Palsy (CP) compared to conventional therapy alone regarding gross motor function, range of motion (ROM) and spasticity. Design: A non-randomized controlled trial conducted in outpatient rehabilitation settings and special education schools, following the recommendations by the Consolidated Standards of Reporting Trials (CONSORT) statement. Participants: Thirty children with CP divided into intervention and control groups. Intervention: The intervention group received three months of therapy (twice per week) with the ATLAS 2030 device in addition to their standard therapy, while the control group underwent standard therapy alone. Main Outcome Measure: Gross motor function assessed using the Gross Motor Function Measure of 88 items (GMFM-88). Secondary Outcomes: Spasticity, measured by the Modified Ashworth Scale (MAS), and ROM of the lower limbs. Results: Statistically significant differences were observed between groups, in favour the intervention group, in both the GMFM-88 total score and dimension A, B and D. Similar findings were noted for spasticity and ROM, demonstrating significant improvements in the intervention group. Conclusion: ATLAS 2030 proves to be a safe and valuable tool for the rehabilitation of children with CP, showing improvements in motor function, spasticity and ROM.